Karakteristik Fisik Daerah Bahaya Banjir Bandang di Kecamatan Lima Kaum, Kabupaten Tanah Datar menggunakan Sistem Informasi Geografis - Novemra, Haykal; Edial, Helfia (TSAQOFAH, 2025)
Lima Kaum Subdistrict possesses physical characteristics that make it highly vulnerable to flash floods, marked by varied topography and complex land use patterns. This study aims to analyze the relationship between physical regional characteristics and land use patterns with the level of flash flood vulnerability, focusing on river buffer zone analysis. The method used is descriptive quantitative, employing thematic map analysis (slope gradient, elevation, rainfall, soil type, land cover, and river density) and direct field observation. The results show that the northern region is dominated by steep slopes, while the southern part is relatively flat. High rainfall is concentrated in the western region, and dominant soil types such as Kambisol Gleik and Gleisol Distrik exhibit poor drainage. Land use patterns indicate rice fields in lowlands and dryland farming in hilly areas. River buffer analysis identifies three flood-prone zones: high-risk (<25 meters), moderate-risk (25–100 meters), and low-risk (100–250 meters). The study concludes that the combination of physical factors and poorly managed land use increases the vulnerability of Lima Kaum Subdistrict to flash floods. These findings serve as a foundation for adaptive and sustainable spatial planning-based disaster mitigation efforts.